2019
DOI: 10.14366/usg.17059
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of shear wave elastography for diagnosing superficial benign soft tissue masses

Abstract: Shear wave elastography may contribute to the differential diagnosis of superficial benign soft tissue masses through a direct quantitative analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 22 publications
4
27
0
Order By: Relevance
“…). In those with a heterogeneous ecostructure, we found a pattern characterized by the alternation of hypo‐ and hyperechoic (laminar) areas in addition to a pattern showing a hyperechoic central area and a surrounding area of different thickness levels – hypoechoic (so‐called target) in accordance with the literature . The morphology was subdivided into round or oval shapes and into regular, lobulated, and irregular margins.…”
Section: Methodssupporting
confidence: 86%
See 3 more Smart Citations
“…). In those with a heterogeneous ecostructure, we found a pattern characterized by the alternation of hypo‐ and hyperechoic (laminar) areas in addition to a pattern showing a hyperechoic central area and a surrounding area of different thickness levels – hypoechoic (so‐called target) in accordance with the literature . The morphology was subdivided into round or oval shapes and into regular, lobulated, and irregular margins.…”
Section: Methodssupporting
confidence: 86%
“…It is for this reason, some studies have evaluated the efficacy of typical Doppler elastosonography and the so-called twinkle artifact in the differential diagnosis of benign skin lesions. 18,20 Conclusion Given the limitations of retrospective series evaluation, our study has confirmed the importance of using high frequency probes in evaluating skin lesions also for sebaceous cysts, for better characterization and, consequently, better differential diagnosis, which is fundamental in patients with multiple and concurrent dermatological diseases in everyday clinical practice. [21][22][23] In our experience with higher frequency probes and in more significant case series, the morphostructural characteristics described in the literature for the diagnosis of so-called sebaceous cysts were confirmed, but moreover it showed the high incidence and diagnostic significance of so-called skin pores, which is a usual finding of these lesions and therefore extremely significant for the differential diagnosis of this disease.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…95 By using SE, compressible ganglion cysts showed a higher strain ratio (2.78 AE 0.48) compared with firmer epidermoid cysts (0.17 AE 0.21). 98,106 With the rupture of an epidermoid cyst, the median shear modulus is decreased. The elasticity of solid lesions can be similar to that of cystic lesions (e.g., lipomatous tumors, ganglion cysts).…”
Section: Strain Elastographymentioning
confidence: 99%